Memory in pregnancy and post‐partum: Item specific and relational encoding processes in recall and recognition. Issue 4 (20th May 2016) - Spataro, Pietro; Saraulli, Daniele; Oriolo, Debora; Costanzi, Marco; Zanetti, Humberto; Cestari, Vincenzo; Rossi‐Arnaud, Clelia
Abstract : It has been recently proposed that pregnant women would perform memory tasks by focusing more on item‐specific processes and less on relational processing, compared to post‐partum women (Mickes, Wixted, Shapiro & Scarff, 2009 ). The present cross‐sectional study tested this hypothesis by directly manipulating the type of encoding employed in the study phase. Pregnant, post‐partum and control women either rated the pleasantness of word meaning (which induced item‐specific elaboration) or named the semantic category to which they belonged (which induced relational elaboration). Memory for the encoded words was later tested in free recall (which emphasizes relational processing) and in recognition (which emphasizes item‐specific processing). In line with Mickes et al .'s (2009 ) conclusions, pregnant women in the item‐specific condition performed worse than post‐partum women in the relational condition in free recall, but not in recognition. However, compared to the other two groups, pregnant women also exhibited lower recognition accuracy in the item‐specific condition. Overall, these results confirm that pregnant women rely on relational encoding less than post‐partum women, but additionally suggest that the former group might use item‐specific processes less efficiently than post‐partum and control women.